Helicobacter pylori Infection and Related Diseases: Clinical Updates and Perspectives - Ikuse, Tamaki; Hojo, Mariko (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Helicobacter pylori is one of the most common infections in the world, affecting roughly half of all humans. Although it is not an infection that causes death immediately after infection, it is one of the largest emerging infectious diseases in the history of humankind, causing a wide variety of diseases and, in the long term, serious complications such as stomach cancer. This Reprint contains empirical studies and reviews regarding the diagnosis, treatment, complications, and management of H. pylori infection, including new diagnostic methods, effective eradication regimens, the management of gastric cancer, and other topics.